Advancing Entrepreneurial Leadership as a Practice in MSME Management and Development. (1st November 2019) - Simba, Amon; Thai, Mai Thi Thanh
Abstract : Consistent with recent studies, we emphasize that entrepreneurial leadership benefits from mutual cross‐fertilization between entrepreneurship and leadership, making it an effective mechanism for studying micro small and medium enterprise (MSME) management and development. Since it is an emerging concept and existing knowledge on MSME management and development so scattered, our comprehensive entrepreneurship and leadership literature review provided us in‐depth insights and new perspectives. From our analysis, a framework emerged mapping a new path for MSMEs. The model presents a nuanced leadership paradigm for small businesses. Thus, by presenting a mechanism that offers new methods aimed at managing and developing MSMEs, we extend existing leadership theories.